2015
DOI: 10.1007/s10157-015-1174-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA double-strand breaks induced intractable glomerular fibrosis in renal allografts

Abstract: Our findings suggest that the long-term RT induces DSBs and HRGEc-secreted COL type VI accumulation in the glomerular capillaries, which might progress to intractable glomerular fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…1a. γ-H2AX was detected in the nuclei of glomerular capillary cells, mainly endothelial cells, as previously reported 7 (Fig. 1a).…”
Section: Dna Damage Is Correlated With Col6 Deposition and Nodular Glsupporting
confidence: 87%
See 3 more Smart Citations
“…1a. γ-H2AX was detected in the nuclei of glomerular capillary cells, mainly endothelial cells, as previously reported 7 (Fig. 1a).…”
Section: Dna Damage Is Correlated With Col6 Deposition and Nodular Glsupporting
confidence: 87%
“…In a previous study, we demonstrated that the presence of DNA damage and COL6 deposition are positively correlated in the glomerulus of renal graft patients 7 . In this study, we examined this correlation in various kidney diseases, especially focusing on those with nodular glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…As well as diabetes nephropathy, FD nephropathy is proteinuric and has a metabolic origin and lyso‐Gb3 was proposed to be a fibrosis promoter in podocytes . Furthermore, DNA damage was recently linked to renal fibrosis and was also found increased in renal cells in a diabetes model …”
Section: Discussionmentioning
confidence: 99%